2014
DOI: 10.4310/jdg/1405447805
|View full text |Cite
|
Sign up to set email alerts
|

Dispersionless integrable systems in 3D and Einstein-Weyl geometry

Abstract: For several classes of second order dispersionless PDEs, we show that the symbols of their formal linearizations define conformal structures which must be EinsteinWeyl in 3D (or self-dual in 4D) if and only if the PDE is integrable by the method of hydrodynamic reductions. This demonstrates that the integrability of these dispersionless PDEs can be seen from the geometry of their formal linearizations.MSC: 35L70, 35Q75, 53C25, 53C80, 53Z05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(134 citation statements)
references
References 55 publications
3
130
0
Order By: Relevance
“…• For every solution of the equation, the symbol of formal linearisation defines an EinsteinWeyl structure [10].…”
Section: Characteristic Integrals Of Second Order Pdes In 3dmentioning
confidence: 99%
“…• For every solution of the equation, the symbol of formal linearisation defines an EinsteinWeyl structure [10].…”
Section: Characteristic Integrals Of Second Order Pdes In 3dmentioning
confidence: 99%
“…where D x k denotes total derivative with respect to the independent variable x k (note that g depends on first-order jets of the solution u, v). Formula (4) appeared in [24] in geometric approach to the dispersionless integrability in 3D. It is invariant under the gauge transformation g → λg, ω → ω + d ln λ, the property characteristic of Einstein-Weyl geometry.…”
Section: Einstein-weyl Geometry In 3dmentioning
confidence: 99%
“…It was shown that the moduli space of integrable equations is 20-dimensional. The recent result of [15], stating that the integrability of a PDE of the form (1) is equivalent to the Einstein-Weyl property of the symbol of its formal linearisation, provides an efficient geometric test of integrability. It was demonstrated in [41] that the coefficients of 'generic' integrable equations (1) can be parametrised by generalized hypergeometric functions.…”
Section: Theoremmentioning
confidence: 99%
“…Although the subject is classical, the following result is new: Since conformal flatness is the necessary condition for integrability, a complete list of linearly degenerate integrable PDEs can be obtained by going through the list of Theorem 3 and either calculating the integrability conditions as derived in [7], or verifying the existence of a Lax pair. Another possibility is to utilise the recent result of [15] …”
Section: Normal Forms Of Quadratic Line Complexes and Linearly Degenementioning
confidence: 99%
See 1 more Smart Citation